Betrayal as Seen in Tinker Tailor Soldier Spy (2011) Movie - Nurmaily, Ely - (SIGEH ELT : Journal of Literature and Linguistics, 2024)
Tinker Tailor Soldier Spy is a 2011 espionage thriller film directed by Tomas Alfredson and based on John le Carré's 1974 novel of the same name. The movie gained critical accolades for its atmospheric directing, scrupulous attention to detail, and stellar cast performances. During the Cold War, the movie depicts a complicated web of espionage and betrayal within the British Secret Intelligence Service (MI6). The research intends to depict betrayal through the agent characters in the movie. The movie was analyzed using qualitative method. The dialogues and narrations are presented in the form of texts. The research integrated several experts’ perspectives on betrayal to assist the writers in revealing the traces of betrayal in the movie. The results of the analysis suggested that the characters conducted acts of betrayal.  The movie has only three sorts of treachery. The first is political betrayal, which is exemplified by Bill Haydon. The second is the romantic betrayal between Ricki Tarr and Irina, Bill Haydon and Ann, which began both relationships due to both agents' personal missions and importance. The third type of betrayal is friendship betrayal which is portrayed by Haydon and Toby. They betray the people who are close to them and have supported them during their hardship